How to take a "portrait" of interpersonal synergies formation? - exemplar data with expert badminton doubles - Passos, P.; Lacasa, E.; Milho, J.; Diniz, A.; Torrents, C. (Ecological Psychology, 2022)
In the last decades, previous research regarding interpersonal synergies formation has emerged under the Uncontrolled Manifold concept, identifying synergies formation based on a single combination of task elements. However, in social systems with redundant degrees of freedom, several combinations to stabilize a performance goal may be the most common picture. Thus, the main goal of this explorative study was to create a "portrait" of a set of task elements combinations (i.e., player`s positions and velocities) adopted to stabilize a performance goal (i.e., interpersonal distance) in expert badminton doubles, which is usually associated with synergies formation. The Uncontrolled Manifold concept was used for that purpose. Our results displayed that the created "portraits" did not display any pattern of interpersonal synergies. Moreover, for all the portraits there were combinations of task elements that had the primacy over the others. A primacy that changed with the rally length. For the shortest and for the longest rallies, the player`s velocity seemed to be more relevant to form interpersonal synergies, whereas for the middle length, both the player`s position and velocity were important for that purpose. Also, there were a decreasing of synergies strength with the increasing of the rally length.